2020
DOI: 10.1111/andr.12952
|View full text |Cite
|
Sign up to set email alerts
|

Does sperm origin—Ejaculated or testicular—Affect embryo morphokinetic parameters?

Abstract: Background It is unclear whether sperm origin, either ejaculated or testicular, in couples diagnosed with male factor infertility, affects the timing of the embryo's developmental events evaluated by time‐lapse monitoring and implantation rates. Objective To examine the effect of sperm origin on embryo morphokinetics in couples diagnosed with male factor infertility. Materials and Methods This study included a retrospective analysis of morphokinetic parameters performed by time‐lapse monitoring between 2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…Our observation on faster pronuclear appearance is in line with earlier observations [ 36 , 37 ]. Sperm DNA damage needs to be repaired in the oocyte after fertilization [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our observation on faster pronuclear appearance is in line with earlier observations [ 36 , 37 ]. Sperm DNA damage needs to be repaired in the oocyte after fertilization [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the impact of normal sperm, impaired ejaculated sperms as well as testicular sperms on early embryo morphokinetics must be considered, especially when the study population is heterogenous, with male and female infertility aetiologies, including azoospermic males where testicular sperms were used to attain fertilization. Differences in morphokinetic parameters on the embryonic cell cycle [ 64 , 65 ], higher aneuploidy rates and mosaicism reported in cases with low sperm concentrations [ 66 ] highlights the need for incorporating sperm origin while developing novel morphokinetic models for embryo selection.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that time of pronuclei appearance and fading and the time to cleavage of two cells for embryos from the nonobstructive azoospermia group was slightly more rapid than embryos from the oligoasthenoteratozoospermia group. However, the time of synchronous four blastomere divisions in the third cell cycle and time to morula in the oligoasthenoteratozoospermia group was signi cantly more rapid than those in the nonobstructive azoospermia group [13].…”
Section: Introductionmentioning
confidence: 85%
“…According to Balaban et al (2001), the use of sperm obtained from the testicles of nonobstructive azoospermia patients reduced blastocyst formation and the implantation rate [12]. Karavani et al (2021) recently compared morphokinetic parameters of embryos between patients with nonobstructive azoospermia versus oligoasthenoteratozoospermia [13]. The study showed that time of pronuclei appearance and fading and the time to cleavage of two cells for embryos from the nonobstructive azoospermia group was slightly more rapid than embryos from the oligoasthenoteratozoospermia group.…”
Section: Introductionmentioning
confidence: 99%